MESIN CARNOT KUANTUM TIGA DIMENSI - , RAHMAT HIDAYAH, Dr. rer. nat. M. Farchani Rosyid ([Yogyakarta] : Universitas Gadjah Mada, 2014)
We have evaluated each quantum thermodynamic process of three dimensional quantum Carnot engine where infinite well potential width Lx